’g’ by Projectile Method - Verma, Manohar Lal (SCHOOL SCIENCE, 2015)
This method is based on the principle of a projectile. Water is projected from a glass tube of narrow internal diameter. This tube is fitted in a vertical plane making an angle ‘a’ to the horizon. It is connected to a constant level water tank by means of a rubber tube. Water is sent at constant pressure in this tube, so that it comes at constant velocity. After leaving the glass tube, the stream of water forms a parabolic path due to gravity.